Individualisation and Resistance at the Coal Face - Peetz, David; Murray, Georgina (Just Labour: A Canadian Journal of Work and Society, 2005)
This paper examines the implementation of a model of systematic individualisation of the employment relationship by a large multinational corporation in Australia, operating with the support of a pro-corporate state, and the nature and effects of resistance. Principally through interviews with affected workers, we show how the symbolic and the real effects of employment practices, relational practices and informational practices were all aimed at removing freedom of association and replacing it with uncontested, union-free managerial control. We consider how workers and their families were affected by these strategies and how they and their union responded. // Cet article examine la mise en place d'un modèle systématique d'individualisation de la relation d'emploi par une grande multinationale australienne, cela avec le support d'un gouvernement partialement favorable au patronat. La nature et l'impact de la résistance des travailleurs syndiqués sont également mis à jour. Nous montrons, principalement à l'appui des témoignages des travailleurs en cause, comment les effets réels ou symboliques des pratiques d'emploi, ceux des pratiques relationnelles et informationnelles ont été utilisés de concert pour dénier la liberté d'association et la remplacer par un contrôle gestionnaire incontestable et exempt de présence syndicale. Nous relatons comment les travailleurs et leurs familles ont souffert de ces stratégies patronales et comment leur syndicat a rétorqué.